MECHANICAL PROPERTIES STUDY OF DURIO ZIBETHINUS SKIN FIBER REINFORCED POLYETHYLENE COMPOSITE - Kuan, Nicholas Hoo Tien; Sam Pek Kee, Law; Mahshuri, Yusof; Sim Nee, Ting; Ng Chee, Khoon (Penerbit UMT, 2022)
Composite materials have been continuously innovated and developed so that they can be improved in almost any criteria as their characteristics are preferable to singlephase materials. Natural fiber reinforced polymer composites can sustainably reduce inorganic and organic wastes, aside from serving as materials with improved mechanical properties. In this study, fiber extracted from Durio zibethinus (durian) skin was examined. Durio zibethinus (DZ) fiber was fabricated into fiber paper sheets and underwent hotpress lamination to produce a composite. This study investigates the differences between fibers extracted from DZ skin and husk. Tensile and micro Vickers tests were performed on the fabricated composites. The results show that the tensile behaviour of the composite fabricated from DZ skin fiber had a value of 20.1 MPa compared with the composite fabricated from a mixture of skin and husk which had a value of 19.4 MPa. These findings suggest that using durian skin resulted in better tensile strength with a FVF (fiber volume fraction) of 18%, compared with using a mixture of skin and husk which had a FVF range of between 8% and 23%. The hardness, meanwhile, increased with the FVF for the composite fabricated from a mixture of DZ skin and husk. This natural fiber composite has the potential to be used in households, automotive parts, lightweight furniture and many other composite engineering applications.